The Disruption of Personal Protection Equipment Supply Chain: What Can We Learn from Global Value Chain in the Time of Covid-19 Outbreak? - Annisa Kirana Andaneswari; Qonitah Rohmadiena (Institute of International Studies, 2020)
Abstract The Covid-19 pandemic has disrupted many aspect of life and it has sought to multifaceted crisis in a global scale. With the continued of health crisis caused by this communicable disease, medical device and personal protection equipment become precious commodity for the general public and healthcare professionals. Therefore, there is a growing demand of Personal Protection Equipment especially face mask and N95 respirators in all over countries. Unfortunately, the decade of expansive trade had been distorted by pandemic of Covid-19 that made the medical supplies cannot meet the global demand. Prior to the outbreak of covid-19, there was an interdependency of medical supplies trade through Global Value Chain. GVC had made the production of medical supplies are effectively fragmented and globally integrated. This article tries to examine the architecture of global medical supply through the lens of Global Value Chain (GVC) before and after pandemic. Using a qualitative methodology this article tries to provide analytical descriptive on global medical devices fragmentation. We use the full UN Comtrade data from 1990 to 2018, Foreign Direct Investment Data from OECD and mass media news to track the shifting of medical devices production during pandemic. The main results indicate that the worsening situation of Pandemic Covid-19 has brought state actors and non-state actors to create new pattern in GVC to provide medical devices worldwide. Finally, this article aims to cast a light on the importance of global cooperation and trade interdependency during crisis.